2021
DOI: 10.1088/1755-1315/788/1/012117
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile of paste, sensory quality, and microstructures surface of patty added with red fruit paste (Pandanus conoideus Lamk)

Abstract: This study aimed to determine the sensory quality and the microstructure surface of the patty added with red fruit paste (RFP). An experimental method was employed with a completely randomized design in this study. The addition of RFP consisted of four treatments with three replications of each treatment. Since RFP was a substitute for animal fat in the patties mixture, the paste levels in the treatment were R0 (control), R1 (5% RFP), R2 (10%), and R3 (15%). Sensory quality was checked by a hedonic test for te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…According to Figure 6, it was found that the most abundant atoms were C 70.4%, O 29.1%, Cl 0.2%, K 0.2%, and Na 0.1%. The prevailing atomic elements are the components of fat, which include a carbon atom (C) and an oxygen atom (O) (Tharukliling et al, 2021). The fat originated from coconut milk added as one of the main ingredients in making Arenga pinnata fruit dodol.…”
Section: -Proximatementioning
confidence: 99%
“…According to Figure 6, it was found that the most abundant atoms were C 70.4%, O 29.1%, Cl 0.2%, K 0.2%, and Na 0.1%. The prevailing atomic elements are the components of fat, which include a carbon atom (C) and an oxygen atom (O) (Tharukliling et al, 2021). The fat originated from coconut milk added as one of the main ingredients in making Arenga pinnata fruit dodol.…”
Section: -Proximatementioning
confidence: 99%